P–756 Predictive factors influencing multiple live births in cumulative IVF cycles: retrospective analysis of over 265000 embryo transfer procedures from the national French registry. (6th August 2021) - Nogueira, D; Keppi, B; Regnier-Vigouroux, G; Scalici, E; Cens, S; Trebesses, L; Malafosse, F; Pierre, S; Montagut, M; Benchaib, M
Abstract: Study question: What are the factors that could predict the number of embryos to be transferred in order to diminish risk of multiple pregnancies? Summary answer: Single embryo transfer (SET) is advisable for <38 year-old women in fresh cycles and for <35 year-old women in FET whatever the IVF number attempts. What is known already: Multiple pregnancies are associated to increased maternal and perinatal complications. Risks associated to multiple implantations are significantly reduced with SET policy. However, while SET is more assertive with a lesser negative impact in younger patients (<35 years), its feasibility is less evident for the older population, whom oocyte quality is likely compromised. A double embryo transfer (DET) could improve chances of implantation and shorten their time to pregnancy. Identification of risk factors for multiple pregnancies could help in decision making for a double or SET and reduce chances for multiple gestations without reducing the chances to achieve pregnancy. Study design, size, duration: A retrospective study from the national French data registry provided and approved by the Agence de la Biomédecine was performed. A total of 196530 fresh and 68913 frozen cycles from women aged 18–43 year-old were included (2014–2017). Risk factors assessed included women's age, number of attempts, number of oocytes, fertilization rate, embryo stage, number of embryos transferred, number of supernumerary embryos frozen. Secondary infertility, oocyte donor, oocyte freezing, PGT, freeze-all and IVM cycles were excluded. Participants/materials, setting, methods: Cumulative cycles derived from 65% of ICSI, 32% of IVF and 3, 2% IVF/ICSI. The distribution of patients age at oocyte retrieval was 60% < 35, 21% < 38, 11% < 40, and 8% ≥ 40 years old. Multivariable logistic regression was conducted to calculate adjusted odds ratios with 95% confidence intervals for live birth chance and multiple live birth risk associated with each risk factor. Main results and the role of chance: The chances of obtaining a cumulative live birth decreases with increased patients age (OR 0.71 for 35–38 years and 0.47 for 38–40 years, p < 0.00001), with increased number of attempts (from OR 0.87 for attempt = 2 to OR 0.74 for attempt ≥ 4, p < 0.00001), and for frozen embryos transferred (OR 0.14, p < 0.00001). The chances of live birth increases with the increased number of oocytes (from OR 1.33 for 4–12 to OR 1.52 for > 18, p < 0.00001 in all cases), with a fertilisation rate >40% (OR 1.29, p < 0.00001), with blastocyst transfer (OR 1.29, p < 0.00001), with the increase on the number of frozen embryos (OR 7.37 for >1, OR 13.08 for >2, and OR 16.92 for >6, p < 0.00001 in all cases) and number of embryos transferred (OR 1.42 for 2 embryos and OR 1.39 for >2 embryos, p < 0.00001 in all cases). In case of live birth, the risks of multiple births when two embryos were transferred decreases in patients aged >38 years (OR 0.50, p < 0.00001) and for frozen embryos transferred (OR 0.65, p < 0.00001). The risk increases with a fertilisation rate >60% (OR 1.30, p < 0.00001), with blastocysts transfer (OR 1.34, p < 0.00001) and when at least one supernumerary embryo is frozen (OR > 1.30, p < 0.00001). Limitations, reasons for caution: This study is limited in only providing a risk-benefit balance for multiples on the choice of transferring one or two embryos. Clinical data such as stimulation protocols and doses of gonadotropins were not considered in this evaluation. Wider implications of the findings: This study provides help to develop a strategy for the medical staff in the decision making for the number of embryos to be transferred. It may also serve as a patient's information aid and help to improve their chances of achieving a health singleton if pregnant. Trial registration number: Not applicable